The initial validation of a novel outcome measure in severe burns- the Persistent Organ Dysfunction +Death: results from a multicenter evaluation - Stoppe, Christian; Hill, Aileen; Day, Andrew G; Kristof, Arnold S; Hundeshagen, Gabriel; Kneser, Ulrich; Beier, Justus; Lumenta, David; Kim, Bong-Sung; Plock, Jan; Collins, Declan P; Gille, Jochen; et al. (Burns, 2021)
Introduction - A need exists to improve the efficiency of clinical trials in burn care. The objective of this study was to validate “Persistent Organ Dysfunction” plus death as endpoint in burn patients and to demonstrate its statistical efficiency. - Methods - This secondary outcome analysis of a dataset from a prospective international multicenter RCT (RE-ENERGIZE) included patients with burned total body surface area >20% and a 6-month follow-up. Persistent organ dysfunction was defined as persistence of organ dysfunction with life-supportiing technologies and ICU care. - Results - In the 539 included patients, the prevalence of 0p p+ pdeath was 40% at day 14 and of 27% at day 28. At both timepoints, survivors with POD (vs. survivors without POD) had a higher mortality rate, longer ICU- and hospital-stays, and a reduced quality of life. POD + death as an endpoint could result in reduced sample size requirements for clinical trials. Detecting a 25% relative risk reduction in 28-day mortality would require a sample size of 4492 patients, whereas 1236 patients would be required were 28-day POD + death used. - Conclusions - POD + death represents a promising composite outcome measure that may reduce the sample size requirements of clinical trials in severe burns patients. Further validation in larger clinical trials is warranted. - Study type - Prospective cohort study, level of evidence: II
Available online 3 October 2020
Gesehen am 09.08.2021